Learning Chemistry with the œRed and Ox Game during Covid-19 Pandemic at SMAN 22 Surabaya - Any Sufiaty; Ryan Hendra Cahyadhi (JCER (Journal of Chemistry Education Research), 2020)
This study aimed to examine the impact of utilizing œRed and Ox Game while Study From Home. Tests were given before and after the student using this game. After that the student have to fulfill some respons after using the game. The results of the study showed this game effectiveness based on students respon obtained 87,73% and there was a significant difference between the average scores before and after learning and it had achieved classical completeness. From aforementioned data, it can be concluded that learning using Red and Ox Game while Study From Home can have an impact on learning of balancing redox equation. This game also can be used as an alternative for teachers so the learning process will be more friendly.